Advances in Boron Isotope Separation by Ion Exchange Chromatography: A Review - Zhao, Hanxue; Gao, Ruichang; Bai, Peng (Asian Journal of Chemistry, 2014)
Boron isotope separation by ion exchange chromatography is characterized by high efficiency, low energy consumption, safe operation and low equipment investment. It is a promising process for industrial scale production. The latest progress for enriching 10B isotope by ion exchange chromatography is reviewed in this article. Currently, strongly basic anion exchange resins, weakly basic anion exchange resins and boron-specific resins are used as chromatographic column packing materials. With a brief introduction of the separation principle, the advantages and disadvantages of these resins are compared. Some elements influencing the single-stage separation factor are also discussed.